PEMANFAATAN WARUNG TUAK DI KABUPATEN ROKAN HULU - Nova Rina Sinaga; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted at 3 Sub district that located in Rokan Hulu regency,namely Kabun sub district, Tandun sub district and Ujung Batu sub district. Thisresearch aims to identify how the utilization of tuak shops and give descriptions aboutcausation factors of the growth of tuak shops in Rokan Hulu regency. This researchentitled “UTILIZATION OF THE TUAK SHOPS ROKAN HULU REGENCY”. Thefoundation of this research is because the researcher perceives lots of tuak shops inRokan Hulu regency and high enthusiasm of locals especially for men visiting tuak shopsevery day. The used type of this research is descriptive quantitative. Samples are theowners and the tuak shop visitors which taken by using census techniques to the shopowners amount 50 respondents that gained from Kabun Sub district, 10 respondentsTandun sub district and 10 respondents from Ujung Batu sub district. Meanwhile,sampling to the visitors of tuak shops is taken by quota sampling techniques bycalculating 10% of 20 visitors of tuak shops are 2 persons the and number of visitors are100 respondents. The data collection of this research was used questionnaires,observation, interview and documentation. The data which has been collected from thisobservation is processed by using frequency table. The result of this research is theutilization of tuak shops are utilized positively and negatively. The positive utilizationmeans utilized by visitors as a place to regroup with counterparts, spending leisure time,having relax and at shops also can find the intimacy, high solidarity. The negativeutilization means some visitors make the tuak shops as a place to have drunks, provokeother people to be a commotion as a prostitution place. The growth factors of tuak shopsin that region are economical factor, social factor, and cultural factor.Keywords : tuak and utilization